Network pharmacology and in silico analysis reveal Kochiae Fructus as a potential therapeutic against atopic dermatitis through immunomodulatory pathway interactions - Shakeel Ahmad Khan (PLoS ONE, 2025)
Atopic dermatitis (AD), a chronic inflammatory disorder, poses significant therapeutic challenges owing to its complex pathophysiology, involving disrupted epidermal barrier function and immune dysregulation. This study investigated the therapeutic potential of Kochiae Fructus in AD treatment using bioinformatics, including network pharmacology and molecular docking techniques. We identified 19 key phytochemicals from Kochiae Fructus and 268 potential targets using the Traditional Chinese Medicine Systems Pharmacology Database (TCMSP) and SwissTarget Prediction. Using GeneCards, 1786 AD-related genes were retrieved, resulting in 116 intersecting gene targets for further analysis. Protein-protein interaction (PPI) networks and Molecular Complex Detection (MCODE) analyses highlighted 78 anti-AD key targets, including SRC, MAPK3, MAPK1, JUN, PIK3CA, ESR1, PTGS2, PTPN11, IL-6, and ALOX5, among the top ten anti-AD core targets. Gene ontology (GO) enrichment analysis revealed that Kochiae Fructus affects biological processes and molecular functions, such as positive regulation of the apoptotic response, inflammatory response, and hormone-mediated signaling pathways, which may be associated with its anti-AD effects. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the C-type lectin receptor signaling pathway is the main pathway involved in the anti-AD effects of Kochiae Fructus, which interacts with a notably larger number of anti-AD core targets and plays a direct role in intensifying crucial inflammatory and immune responses in the heart of AD pathogenesis. Molecular docking demonstrated robust binding affinities of key phytochemicals, particularly ecdysterone and 11,14-eicosadienoic acid, to the anti-AD core targets. Molecular dynamics simulations of over 1000 ns confirmed the stability and potential efficacy of these interactions. Hence, this study underscores the therapeutic potential of Kochiae Fructus in AD management, offering a mechanistic basis for its clinical application and paving the way for novel anti-AD strategies that leverage TCM phytochemicals.